2019
DOI: 10.5713/ajas.18.0965
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and flavor compounds of pork meat as a function of carcass quality grade

Abstract: Objective The present work aimed at evaluating the effects of carcass quality grade (QG) on the quality characteristics of pork meat according to Korean carcass QG system. Methods Pork carcasses with varying in QG: 1+ (QG1+, n = 10), 1 (QG1, n = 10) and 2 (QG2, n = 10), were used to evaluate the relationship between carcass QG and meat quality. The meat quality traits, fatty acid profiles, flavor compounds and sensory qualities were measured on the longiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 29 publications
(44 reference statements)
5
32
0
Order By: Relevance
“…Based on their chemical families, these compounds were classified into the follow ing classes: aldehydes (17), alcohols (8), pyrazines (5), sulfur containing compounds (5), furans (2), and hydrocarbons (11). Aldehydes were the most predominant class found in this study, which agrees well with the finding of Kim et al [35] and Ba et al [25]. Previous studies have reported that alde hydes associated with green, fatty and fruity odor notes at very low odor detection threshold are important in the develop ment of flavor characteristics cooked meat [34,36].…”
Section: Effects Of Ageing and Cooking Treatment On Volatile Flavor Csupporting
confidence: 90%
See 3 more Smart Citations
“…Based on their chemical families, these compounds were classified into the follow ing classes: aldehydes (17), alcohols (8), pyrazines (5), sulfur containing compounds (5), furans (2), and hydrocarbons (11). Aldehydes were the most predominant class found in this study, which agrees well with the finding of Kim et al [35] and Ba et al [25]. Previous studies have reported that alde hydes associated with green, fatty and fruity odor notes at very low odor detection threshold are important in the develop ment of flavor characteristics cooked meat [34,36].…”
Section: Effects Of Ageing and Cooking Treatment On Volatile Flavor Csupporting
confidence: 90%
“…No statistical differences occurred among the SV, SV+OV and SV+TC for all the compounds (p>0.05). In general, most of these sulfurcontaining com pounds have been reported for cooked meats [25,40]. The ageing apparently had a minor effect on the sulfurcontaining compounds; 2thiophen methanol increased in its amount, and 3phenyl thiophene decreased in its amount in the sam ples treated with the SV+TC and SV+OV, respectively after 14 d ageing (p<0.05).…”
Section: Effects Of Ageing and Cooking Treatment On Volatile Flavor Cmentioning
confidence: 91%
See 2 more Smart Citations
“…The carcass grading, therefore, is an important step and is the basis to determine the final market price for each finishing pig. Till now, there have been several studies assessing the effects of QG on the pork meat quality ( Van Ba et al, 2019 ), however, these authors usually used the LD muscles as the representative samples in their studies. Though the belly and shoulder butt are considered as the most economically important and preferable pork cuts, no studies were conducted to investigate whether the QG affects their technological and eating qualities.…”
Section: Introductionmentioning
confidence: 99%